Distinct persistence barriers in two types of ENSO - Ren, Hong‐Li; Jin, Fei‐Fei; Tian, Ben; Scaife, Adam A. (Geophysical research letters, 2016)
El Niño–Southern Oscillation (ENSO) is usually subject to a persistence barrier (PB) in boreal spring. This study quantifies the PB and then reveals its distinct features in the two types of ENSO, the eastern Pacific (EP) and central Pacific (CP) types. We suggest that the PB of ENSO can be measured by the maximum rate of autocorrelation decline of Niño sea surface temperature anomaly (SSTA) indices. Results show that the PB of ENSO generally occurs in boreal late spring to early summer in terms of Niño3.4 index, and the EP ENSO has the PB in late spring, while the CP type has the PB in summer. By defining an index to quantify PB intensity of ENSO, we find that the CP ENSO type features a much weaker PB, compared to the EP type, and the PB intensity of equatorial SSTAs is larger over the EP than the western Pacific and the far EP. Key Points Quantify the persistence barrier of ENSO and reveal its intensity for the two ENSO types in terms of the fastest loss of SSTA persistence Persistence barrier of the eastern Pacific ENSO type is in boreal late spring while that of the central Pacific ENSO type in summer The persistence barrier of ENSO is much weaker in the CP than EP type, and its intensity varies with longitude and maximizes in EP region